Evoked Potentials and EEG Analysis in Rett Syndrome and Related Developmental Encephalopathies: Towards a Biomarker for Translational Research - Saby, Joni N.; Peters, Sarika U.; Roberts, Timothy P. L.; Nelson, Charles A.; Marsh, Eric D. (Frontiers in Integrative Neuroscience, 2020)
Rett syndrome is a debilitating neurodevelopmental disorder for which no disease modifying treatment is available. Fortunately, advances in our understanding of the genetics and pathophysiology of Rett syndrome has led to the development of promising new therapeutics for the condition. Several of these therapeutics are currently being tested in clinical trials with patient groups with others likely to progress to clinical trials in the coming years. The failure of recent clinical trials for Rett syndrome and other neurodevelopmental disorders has highlighted the need for electrophysiological or other objective biological markers of treatment response to support the success of clinical trials moving forward. The purpose of this review is to describe the existing studies of electroencephalography and evoked potentials in Rett syndrome and discuss the open questions that must be addressed before the field is able to adopt these measures as surrogate endpoints in clinical trials. In addition to summarizing the human work on Rett syndrome, we also describe relevant studies with animal models and the limited research that has been carried out on Rett-related disorders, particularly MECP2 duplication syndrome, CDKL5 disorder, and FOXG1 disorder.